PENGARUH MEDIA TELEVISI TERHADAP KEPUTUSAN PEMBELIAN DAN LOYALITAS PRODUK IKLAN DI WILAYAH EKS KARISIDENAN BESUKI JAWA TIMUR - Nanik Hariyana (UPT Penerbitan Universitas Jember)
The purpose of this study to determine Television Toward Purchase Decision and Product Loyalty rent in Region Ex Karisidenan Besuki East Java, phenomena of this study is the purchasing power of communities in East Java Besuki Ex Karisidenan in The purchase decisions and product loyalty television media. Purposive sampling is used to collect information with a sample of 130 respondents with his measuring instrument SEM results indicate that there is significant influence Variable Television Toward Purchase Decision and Product Loyalty rent in Region Ex Karisidenan Besuki East Java tends to increase at a rate of 5% alpha.